Hubungan Jam Mengemudi, Tekanan Darah, dan Agresivitas Mengemudi terhadap Kelelahan pada Pengemudi Bus AKDP: Studi Cross-Sectional - Firsta Vian Rahmadani; Bayu Yoni Setyo Nugroho (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2026)
Intercity bus drivers (AKDP) in Indonesia operate under high occupational demands with limited regulatory enforcement. National road traffic data identify driver fatigue as a primary contributing factor to accidents; however, empirical evidence specifically targeting AKDP drivers remains scarce. To analyze the associations between driving hours, blood pressure status, and aggressive driving behavior with fatigue among AKDP bus drivers, and to identify dominant predictors of fatigue through multivariate analysis. A cross-sectional study was conducted among 63 AKDP bus drivers from five bus companies (PO). Fatigue was assessed using the three-dimensional Industrial Fatigue Research Committee (IFRC) questionnaire covering activity weakening, motivational weakening, and physical fatigue. Aggressive driving was evaluated via behavioral questionnaire; blood pressure was measured directly. Bivariate Chi-Square tests and multivariate logistic regression were applied. A total of 77.8% of drivers exceeded the regulatory limit of 8 hours/day (PM 83/2018), with a mean of 12.03 hours/day (SD=2.91). The prevalence of abnormal blood pressure reached 95.2%, and 40.3% exhibited unsafe driving behavior. Logistic regression identified driving hours as the dominant predictor of fatigue (OR=15.28; 95% CI: 8.51-18.96). No significant associations were found between aggressive driving and driving hours (p=0.893) or blood pressure (p=0.798). Conclusion: Driving hour violations are systemic and constitute the strongest predictor of fatigue among AKDP bus drivers. The alarmingly high prevalence of blood pressure abnormalities signals a serious cardiovascular burden requiring immediate intervention. Priority measures include mandatory digital tachograph enforcement, periodic health screening, and integrated fatigue management training.